Module Development of Ceremony Food for Javanese Ethnic in Johor - Abdul Rahman, Abdul Wafi; Ibrahim, Sofea; Md Sahak, Adibah Aishah; Raden Ismail, Raden Mohd Farhan Helmy (Research and Innovation in Technical and Vocational Education and Training, 2024)
The development of the Javanese Ethnic Food Module in Johor has helped educators as well as students throughout the teaching and learning process and has been a source of reference for both faculty and students. However, the main problem is that there is no complete source of reference for the subject of Malay Cuisine especially on ceremonies of Javanese cuisine. In addition, the absence of modules for this subject is also a problem during the teaching and learning process. Therefore, the purpose of this study is to develop a Java Ethnic Food Module In Johor to educate students, and the public, especially those taking Culinary Art courses. This study uses quantitative methods in which the data will be evaluated based on the average percentage of expert evaluators based on the expert evaluation form. The development of this module aims to assess the suitability of the content, format, clarity, and design of the module for the use of teachers and students in the Culinary field during the learning process. This module has been evaluated using an expert evaluation form by 5 field experts, a Culinary Lecturer at the Faculty of Technical and Vocational Education, University Tun Hussien Onn Malaysia. By using the average percentage value, the results have shown that the level of suitability in terms of content, format, clarity, and design of the module is at a high level where the overall average percentage value is 96 percent. So it is suitable for development and use by lecturers and students especially in the field of Culinary. In conclusion, the development of the learning module for the subject of Malay Cuisine is suitable for development based on expert feedback. In addition, the development of this module will help lecturers as well as students during the study session as well as a source of reference.